2007
DOI: 10.1364/ol.32.001725
|View full text |Cite
|
Sign up to set email alerts
|

Coherent versus incoherent Raman scattering: molecular coherence excitation and measurement

Abstract: We present a comparative analysis of spontaneous and coherent Raman scattering on pyridine. The instantaneous excitation of the molecular coherence is done by a pair of ultrashort preparation pulses. Then, a long narrowband probe pulse is scattered off the molecular vibrations. The described hybrid technique allows for the single-shot acquisition of a background-free coherent Raman spectrum within the excitation band and its straightforward comparison with the spontaneous Raman measurements, performed in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 10 publications
3
52
0
Order By: Relevance
“…Based on the theory of Tolles et al 6 , we have obtained reasonable theoretical agreement with the experimental results we present here 12 . Our measurements are also in reasonable agreement with recent reports comparing coherent and spontaneous Raman scattering 7,8 . The signal strength advantages provided by coherent methods are mitigated by the low incident power, short interaction lengths, and low concentrations used in biological imaging.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Based on the theory of Tolles et al 6 , we have obtained reasonable theoretical agreement with the experimental results we present here 12 . Our measurements are also in reasonable agreement with recent reports comparing coherent and spontaneous Raman scattering 7,8 . The signal strength advantages provided by coherent methods are mitigated by the low incident power, short interaction lengths, and low concentrations used in biological imaging.…”
Section: Discussionsupporting
confidence: 93%
“…To make our comparison between coherent and spontaneous Raman scattering, we use the time-delayed, three-color CSRS approach similar to that of Scully et al 7,8 , shown in Figure 1. In this method, a time delay is introduced between the pump pulses and the probe pulse, suppressing the nonresonant background that decays rapidly as a function of delay due to its instantaneous electronic nature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The five-orders-of-magnitude increase in the pulse repetition rate accompanied by four-orders-of-magnitude decrease in the pulse energy (compared to Ref. [1][2][3]) makes our new system well-suited for coherent Raman microscopy, where lower-energy pulses are naturally needed to avoid laser-induced sample damage.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a so-called hybrid CARS technique has been developed [7] and applied to micro-spectroscopy and imaging, with a simplified system based on a femtosecond Ti:sapphire laser oscillator [8]. In addition, related techniques have been developed and used on a number of samples [9][10][11][12][13][14][15][16], and a special emphasis has been made on the enhancement obtained through preparation of a substantial molecular coherence [17][18][19]. Now we demonstrate that the oscillator-based hybrid CARS micro-spectroscopy can be conducted in epi-detection (back-scattering) configuration, which may have potential implications for hybrid CARS microscopy on opaque samples where the forward-propagating signal cannot be collected.…”
mentioning
confidence: 99%